The expanding reaction toolkit for DNA-encoded libraries. (1st November 2021) - Fair, Richard J.; Walsh, Ryan T.; Hupp, Christopher D.
Graphical abstract: Abstract: Over the past decade, DNA-encoded libraries (DELs) have emerged as a leading platform for small molecule drug discovery among pharmaceutical companies, biotech companies and academic drug hunters alike. This revolutionary technology has tremendous potential that is yet to be fully realized, as the exploration of therapeutically relevant chemical space is fueled by the ever-expanding repertoire of DNA-compatible reactions used to construct the libraries. Advances in direct coupling reactions, like photo-catalytic cross couplings, unique cyclizations such as the formation of 1, 2, 4–oxadiazoles, and new functional group transformations are valuable contributions to the DEL reaction toolkit, and indicate where future reaction development efforts should focus in order to maximize the productivity of DELs.